Attitudes of nursing students towards LGBT individuals and the affecting factors. Issue 1 (28th August 2021) - Özdemir, Rana Can; Erenoğlu, Rabiye
Abstract: Purpose: To determine the attitudes of nursing students towards LGBT (lesbian, gay, bisexual, and transgender) individuals and the affecting factors. Design and Method: The universe of the research consisted of 500 students. The data collection tools used were "Demographic Data Form" and "Attitude towards Lesbians and Gay Men Scale (ATLG)." Findings: Students' attitudes towards LGBT individuals are at a medium level. Male participants had more negative attitudes towards LGBT individuals. Practical Implications: Nurses should provide services within the framework of professional values. In this context, vulnerable groups should be handled carefully. Awareness should be created among nurses.